THE ROLE OF .NET CORE MACHINE LEARNING AND AI IN EDUCATION: PERSONALIZED LEARNING - Jagdip Keshavlal Jadav, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the transformative impact of .NET Core, Machine Learning (ML), and Artificial Intelligence (AI) in revolutionizing personalized learning within educational environments. The article examines various aspects of AI-driven educational technology, including content adaptation, data-driven insights for teachers, predictive modeling for early intervention, automated content recommendations, real-time assessment systems, gamification strategies, and support for diverse learners. Through extensive research across multiple educational institutions, the analysis demonstrates how ML.NET's capabilities have enhanced student engagement, improved learning outcomes, reduced achievement gaps, and enabled more effective teaching methodologies. The findings highlight the significant advancements in personalized education through intelligent content delivery, adaptive assessment systems, and real-time intervention strategies.